The level of patient satisfaction with nursing care in hospital wards - Sierpińska, Lidia; Dzirba, Alina (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2011)
Introduction: The evaluation of patients’ satisfaction with hospitalization, and the identification of their requirements are pivotal in the management of health establishments. The introduction of the quality management system in hospitals provides opportunities for improving medical services and fulfilling customers’ needs. These objectives can be achieved by effective methods, techniques and tools. An example of identifying patient’s expectations during hospitalization is a survey (with the aid of a questionnaire) on the level of patient satisfaction. Aim of the study: Evaluate the level of patient satisfaction with care nursing care in hospital wards as a determinant of the process of optimization of the nursing quality management. Material and methods: The study was conducted in the first half of 2010 among 112 patients treated in three hospital wards (surgical, urology, orthopedic) of the 1st Military Hospital with the SP ZOZ Outpatient Dep. in Lublin. The diagnostic survey method was used in the research, with the help of an anonymous questionnaire. Results : The obtained results allow to identify the strengths and weaknesses of nursing care in hospital wards from the recipient’s perspective. The area of nursing care was evaluated very well in general and in detail. Many respondents gave arguments for high ratings. Few respondents rated low and very low the care of patients in the individual criteria, and a few expressed criticisms. Conclusions : Although the evaluation of the level of patient satisfaction in hospital wards is subjective, it should be monitored systematically, as it helps the staff to establish the needs of patients.